Mucosal-associated invariant T cells in cancer: dual roles, complex interactions and therapeutic potential - Yigit, Mesut; Basoglu, Omer Faruk; Unutmaz, Derya (Frontiers in Immunology, 2024)
Mucosal-associated invariant T (MAIT) cells play diverse roles in cancer, infectious diseases, and immunotherapy. This review explores their intricate involvement in cancer, from early detection to their dual functions in promoting inflammation and mediating antitumor responses. Within the solid tumor microenvironment (TME), MAIT cells can acquire an 'exhausted' state and secrete tumor-promoting cytokines. On the other hand, MAIT cells are highly cytotoxic, and there is evidence that they may have an anti-tumor immune response. The frequency of MAIT cells and their subsets has also been shown to have prognostic value in several cancer types. Recent innovative approaches, such as programming MAIT cells with chimeric antigen receptors (CARs), provide a novel and exciting approach to utilizing these cells in cell-based cancer immunotherapy. Because MAIT cells have a restricted T cell receptor (TCR) and recognize a common antigen, this also mitigates potential graft-versus-host disease (GVHD) and opens the possibility of using allogeneic MAIT cells as off-the-shelf cell therapies in cancer. Additionally, we outline the interactions of MAIT cells with the microbiome and their critical role in infectious diseases and how this may impact the tumor responses of these cells.Understanding these complex roles can lead to novel therapeutic strategies harnessing the targeting capabilities of MAIT cells.